Effects of Nitrogen Limitation on Dunaliella sp.–Alteromonas sp. Interactions: From Mutualistic to Competitive Relationships - Le Chevanton, Myriam; Garnier, Matthieu; Lukomska, Ewa; Schreiber, Nathalie; Cadoret, Jean-Paul; Saint-Jean, Bruno; Bougaran, Gaël (Frontiers in Marine Science, 2016)
Interactions between photosynthetic and non-photosynthetic microorganisms play an essential role in natural aquatic environments and the contribution of bacteria and microalgae to the nitrogen cycle can lead to both competitive and mutualistic relationships. Nitrogen is considered to be, with phosphorus and iron, one of the main limiting nutrients for primary production in the oceans and its availability experiences large temporal and geographical variations. For these reasons, it is important to understand how competitive and mutualistic interactions between photosynthetic and heterotrophic microorganisms are impacted by nitrogen limitation. In a previous study performed in batch cultures, the addition of a selected bacterial strain of Alteromonas sp. resulted in a final biomass increase in the green alga Dunaliella sp. as a result of higher nitrogen incorporation into the algal cells. The present work focuses on testing the potential of the same microalgae–bacteria association and nitrogen interactions in chemostats limited by nitrogen. Axenic and mixed cultures were compared at two dilution rates to evaluate the impact of nitrogen limitation on interactions. The addition of bacteria resulted in increased cell size in the microalgae, as well as decreased carbon incorporation, which was exacerbated by high nitrogen limitation. Biochemical analyses for the different components including microalgae, bacteria, non-living particulate matter, and dissolved organic matter, suggested that bacteria uptake carbon from carbon-rich particulate matter released by microalgae. Dissolved organic nitrogen released by microalgae was apparently not taken up by bacteria, which casts doubt on the remineralization of dissolved organic nitrogen by Alteromonas sp. in chemostats. Dunaliella sp. obtained ammonium-nitrogen more efficiently under lower nitrogen limitation. Overall, we revealed competition between microalgae and bacteria for ammonium when this was in continuous but limited supply. Competition for mineral nitrogen increased with nitrogen limitation. From our study we suggest that competitive or mutualistic relationships between microalgae and bacteria largely depend on the ecophysiological status of the two microorganisms. The outcome of microalgae–bacteria interactions in natural and artificial ecosystems largely depends on environmental factors. Our results indicate the need to improve understanding of the interaction/s between these microbial players.